Assessment of interleukin-10 promoter variant (−1082A/G) and cytokine production in patients with hemolytic uremic syndrome - Mongelos, Micaela Aldana; Sosa, Fernando Nicolás; Pineda, Gonzalo Ezequiel; Fiorentino, Gabriela; Santiago, Adriana; Abelleyro, Miguel Martín; Rossetti, Liliana Carmen; Exeni, Ramón; De Brasi, Carlos Daniel; Palermo, Marina Sandra; Ramos, María Victoria (Frontiers in Pediatrics, 2023)
Introduction Hemolytic uremic syndrome (HUS) is a condition that results in acute kidney failure mainly in children, which is caused by Shiga toxin–producing Escherichia coli and inflammatory response. Although anti-inflammatory mechanisms are triggered, studies on the implication in HUS are scarce. Interleukin-10 (IL-10) regulates inflammation in vivo, and the interindividual differences in its expression are related to genetic variants. Notably, the single nucleotide polymorphism (SNP) rs1800896 −1082 (A/G), located in the IL-10 promoter, regulates cytokine expression. Methods Plasma and peripheral blood mononuclear cells (PBMC) were collected from healthy children and HUS patients exhibiting hemolytic anemia, thrombocytopenia, and kidney damage. Monocytes identified as CD14+ cells were analyzed within PBMC by flow cytometry. IL-10 levels were quantified by ELISA, and SNP −1082 (A/G) was analyzed by allele-specific PCR. Results Circulating IL-10 levels were increased in HUS patients, but PBMC from these patients exhibited a lower capacity to secrete this cytokine compared with those from healthy children. Interestingly, there was a negative association between the circulating levels of IL-10 and inflammatory cytokine IL-8. We observed that circulating IL-10 levels were threefold higher in HUS patients with −1082G allele in comparison to AA genotype. Moreover, there was relative enrichment of GG/AG genotypes in HUS patients with severe kidney failure. Discussion Our results suggest a possible contribution of SNP −1082 (A/G) to the severity of kidney failure in HUS patients that should be further evaluated in a larger cohort.